Internet and the structure of public revenue: Resource revenue versus non-resource revenue - Sèna Kimm Gnangnon; Jean-François Brun (Journal of Economic Structures, 2019)
This paper examines whether the Internet has led to a shift from reliance on resource revenue towards progressive reliance on non-resource revenue, which is ultimately a sustainable source of public revenue. The analysis has been carried out using a sample of 99 countries, including both developed and developing countries, over 1995-2015. Empirical results obtained from the use of the two-step system GMM approach suggest that the Internet induces a change in the structure of public revenue, in particular from resource revenue towards non-resource revenue. In addition, this effect is higher for less advanced countries than for more advanced economies. Thus, the Internet could be a powerful tool for governments to reduce their dependence on resource revenue, in particular in resource-rich countries.
Keywords: H1; O3; Q33; Q38; 330; Internet; Resource revenue; Non-resource revenue